2004
DOI: 10.1128/jcm.42.5.2144-2151.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “Helicobacter heilmannii” Subtypes in the Gastric Mucosas of Cats and Dogs

Abstract: Infection with candidatus "Helicobacter heilmannii" is associated with gastritis and mucosa-associated lymphoid tissue lymphoma in people. Infection with "H. heilmannii" type 1 predominates (80%) and is thought to be acquired from dogs, cats, or pigs. We further examined the zoonotic potential of dogs and cats by amplifying gastric DNA from cats (n ‫؍‬ 45) and dogs (n ‫؍‬ 10) with primers against "H. heilmannii" ureB and 16S rRNA genes and sequencing the products. Fluorescence in situ hybridization (FISH) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 31 publications
2
62
2
5
Order By: Relevance
“…In humans, oral-oral, fecal-oral and gastro-oral routes of transmission are suspected, while the oral cavity is thought to serve as the reservoir of the bacteria (Agüloǧlu et al 2006, Cellini et al 2010, Abdel-Raouf et al 2014. Other species of Helicobacter may be the cause of gastritis in 0.25 -4% of humans (Priestnall et al 2004). Therefore, it is thought that dogs and cats are risk factors of a Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, oral-oral, fecal-oral and gastro-oral routes of transmission are suspected, while the oral cavity is thought to serve as the reservoir of the bacteria (Agüloǧlu et al 2006, Cellini et al 2010, Abdel-Raouf et al 2014. Other species of Helicobacter may be the cause of gastritis in 0.25 -4% of humans (Priestnall et al 2004). Therefore, it is thought that dogs and cats are risk factors of a Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the prevalence of various species of Helicobacter in the canine stomach seem to confirm this finding. The most common species identified in Finland, the United States and Belgium is Helicobacter bizzozeronii (Jalava et al 1997, Priestnall et al 2004, Bulck et al 2005. Helicobacter salomonis is the most commonly found species in Sweden (Ekman et al 2013), while Helicobacter heilmannii is the most recognized species in Poland, Portugal and South Korea (Hwang et al 2002, Kubiak 2006, Amorim et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…An early study used several detection techniques and showed that the stomach of 91% of pet cats (n=58) were positive for the genus Helicobacter (Neiger et al 1998), suggesting a high occurrence of this bacterial group in the feline stomach. In another study, it was shown that cats and dogs are predominantly coloniszed by H. heilmannii (Priestnall et al 2004) but other species (e.g., H. felis, H. bizzozeronii, H. salomonis, H. pametensis) have also been identified in these animal species (Neiger and Simpson 2000).…”
Section: The Gi Microbiota Of Catsmentioning
confidence: 99%
“…Currently, the most accurate method available for conclusive species identification is the use of PCR, followed by sequencing of specific target genes. These include the urease A and B (ureA, ureB) genes, the heat shock protein 60 (hsp60) gene, and the gyrase subunit B (gyrB) gene [44,[71][72][73][74] . Sequencing of the 16S rRNA gene and of the 23S rRNA gene allows distinction of H. suis from the rest of the H. heilmannii s.l.…”
Section: Diagnosismentioning
confidence: 99%